Special Broadcast: Marie Brooks Caribbean Dance Theatre (African Knowledges and the History Publication since the 1970s)
A Special talk show in honor of Marie Brooks, legendary dancer and Choreographer of Afro-Caribbean dance.
Keywords: Dance; Culture